Nonmetal clasp dentures: What is the evidence about their use? - Inti Mendoza-Carrasco; Juliana Hotta; Carolina Yoshi Campos Sugio; Andréa Lemos Falcao Procópio; Vanessa Migliorini Urban; Victor Mosquim; Gerson Aparecido Foratori-Junior; Simone Soares; Karin Hermana Neppelenbroek (Wolters Kluwer Medknow Publications, 2020)
The aim was to discuss the indications, contraindications, advantages, and disadvantages of Nonmetal clasp dentures (NMCDs), as well as the most relevant properties of its constituent materials. A search was conducted using the keywords: "nonmetal clasp dentures," "thermoplastic resin," "flexible resin removable partial denture," "polyamide," and "nylon" in databases PubMed/Medline, Lilacs, SciELO, and textbooks between 1955 and 2020. Theses and texts without reliable sources of publication were excluded. Once the analysis instruments were determined, the data were analyzed and discussed. NMCDs present high flexibility, easy adaptation to the abutments, color compatibility and biocompatibility with the oral mucosa, and absence of visible metal clasps. However, they need laboratory relining, grinding, and polishing, do not have criteria for its planning, become rougher and stained over time, and are able to traumatize supporting tissues. The association with metal components seems to be an alternative to increase the success of NMCDs by combining esthetics and biomechanical principles of conventional removable partial dentures. The lack of long-term clinical studies makes the professionals to rely solely on previous experiences or on the manufacturers' recommendations. It suggested that NMCDs must be indicated with caution when not used temporarily.